1998
DOI: 10.1073/pnas.95.14.7860
|View full text |Cite|
|
Sign up to set email alerts
|

Genes from mycoparasitic fungi as a source for improving plant resistance to fungal pathogens

Abstract: Disease resistance in transgenic plants has been improved, for the first time, by the insertion of a gene from a biocontrol fungus. The gene encoding a strongly antifungal endochitinase from the mycoparasitic fungus Trichoderma harzianum was transferred to tobacco and potato. High expression levels of the fungal gene were obtained in different plant tissues, which had no visible effect on plant growth and development. Substantial differences in endochitinase activity were detected among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
237
0
6

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 402 publications
(255 citation statements)
references
References 32 publications
12
237
0
6
Order By: Relevance
“…However, in the present study, none of the transgenic plants of tobacco and tomato, expressing endochitinase showed morphological abnormalities. This result is in agreement with the earlier reports (Lorito et al, 1998;Mora and Earle, 2001;Emani et al, 2003), where endochitinase expression did not adversely affect the plant phenotype.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…However, in the present study, none of the transgenic plants of tobacco and tomato, expressing endochitinase showed morphological abnormalities. This result is in agreement with the earlier reports (Lorito et al, 1998;Mora and Earle, 2001;Emani et al, 2003), where endochitinase expression did not adversely affect the plant phenotype.…”
Section: Discussionsupporting
confidence: 94%
“…The pathogens used in the present study have been widely used in the disease resistance assay (Terakawa et al, 1997;Chakrabarti et al, 2003;Jang et al 2006). Transgenic plants with endochitiase gene from T. harzianum have shown enhanced resistance to B. cinerea and A. alternata (Lorito et al, 1998). Transgenic broccoli plants also showed moderate level of disease resistance (Mora and Earle, 2001), Transgenic apple showed reduced disease severity from 0-99.7 % (number of lesions) or 0-90 % (percentage leaf area infected) (Bolar et al, 2000).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In planta expression of endochitinase genes from diverse fungi, such as Trichoderma harzianum ( Lorito et al ., 1998) and Rhizopus oligosporus (Terekawa et al ., 1997), has proven to be more effective both in terms of the level and in the spectrum of fungal pathogen resistance compared to the plant-derived chitinases. In addition to the direct action of chitinases on the cell wall of an invading pathogen, it has been suggested that the fungal cell wall fragments released as a result of extracellular chitinase activity may in turn activate a number of defensive responses in plants (Grison et al ., 1996;Lorito et al ., 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Advances in genetic engineering have made possible the development of plants with new predictable phenotypes [1,2]. In particular, to increase resistance against diseases, different genetic strategies have been proposed, which include utilization of antibacterial proteins of both plant [3][4][5] and non-plant origin [6,7].…”
Section: Introductionmentioning
confidence: 99%